Combined Management of Apical Root Fracture and Avulsion of Two Maxillary Permanent Central Incisors: A Case Report - Giulia Bardini; Davide Musu; Silvia Mezzena; Claudia Dettori; Elisabetta Cotti (MDPI AG, 2021)
As a result of a skiing accident, a ten-year-old girl suffered combined injuries to both maxillary central incisor teeth (#1.1 and #2.1). The injuries were uncomplicated crown fractures, apical horizontal root fractures, and a severe extrusive luxation of the coronal segments of the teeth. Her mother repositioned the teeth immediately, resulting in good initial healing. Nine months later, the patient was referred to a specialist to manage the endodontic consequences of the trauma. The apexification treatment of the fractured roots, using a preformed apical barrier technique with bioactive cement, was the treatment of choice, administered to both the avulsed roots at two separate recall visits. The best option for managing the fractured apical segments was to continue with the follow-up, which was conducted to assess the overall case at 30 months. The fractured apexes remained normally positioned inside the socket and were asymptomatic (as they presumably maintained a physiological vascular-nerve supply and, consequently, their vitality), while the apexification treatment led to the healing of the periodontal tissues and to hard tissue formation in the area of the interrupted roots in the avulsed portion of the teeth. The management of traumatic injuries in teeth often requires multiple treatment approaches, because these injuries rarely represent one single type of trauma.